Quantitative evaluation of increased overpressure from tectonic compression stress and its significance—A case study from the Dabei Gas Field in Kuqa Depression - Gang Wang; Chang-Yu Fan; Zhen-Liang Wang; Hai-Jun Yang; Qing-Kuan Wu (Energy Exploration & Exploitation)
Increased overpressure from tectonic compression stress (IOTCS) plays a key role in rock deformation, seismic activity, and hydrocarbon migration in sedimentary basins. However, the coupled evolution of stress, strain, and pressure during IOTCS remains unclear. The key parameters in existing quantitative evaluation methods of IOTCS are difficult to obtain accurately. Tectonic compression deformation occurs in three stages: volumetric strain, distortion, and rupture, with IOTCS primarily in the first two stages. We developed a constitutive effective stress model for the Coulomb failure stage, combined with plane stress field simulations, to quantitatively calculate IOTCS. This clarifies the stress–strain–pressure coupling process, and provides a quantitative evaluation model with high applicability and accuracy. Applied to the Dabei Gas Field, the results show: (a) IOTCS ranges from 80 to 220 MPa with a 6% relative error compared to aqueous inclusions pressures, indicating high accuracy; (b) IOTCS limits shear fracture development, leading to high fracture density in low fluid pressure zones; and (c) IOTCS increases the driving force for hydrocarbon migration by 1.8 to 2.1 times compared to non-IOTCS conditions.